Preface : A Negotiation Space of the Translator in Postcolonial Context from Case Study in the Translations of Dan-aran Saengthong - เฉลิมแสนยากร จิรัฏฐ์ (Journal of the Faculty of Arts, Silpakorn University, 2020)
The purpose of this article is to analyze “the prefaces” from five translation works of Dan-aran Saengthong : Ernest Hemingway’s The Sun Also Rises and The Garden of Eden, Charles Portis’s True Grit, Knut Hamsun’s Hunger and a short story by Jorge Luis Borges; Street Corner Man. The study showed that the purposes of the prefaces were categorized into two periods of works. The prefaces in the first period of his works are from The Sun Also Rises and The Garden of Eden and True Grit. The translator expressed his honest attitude to the original works by clarifying the technical terms and recommending the original works to readers rather than the translated versions. The translator criticized some imperfection in the works of the writers in the prefaces in the second period of his works from Hunger and Street Corner Man. The translator also openly expressed his personal attitude by adapting the original versions. Furthermore, the translator simplified the local context for Thai readers. Therefore, the prefaces in the second period of his works apparently showed a negotiation space of the differences between the original works and translated versions, and also the authorship of the writers and the translators.